The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1021/ja990954t
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of the Additions of Germylenes to Ethylene

Abstract: Complete geometry optimizations were carried out using density functional theory to study the potential energy surfaces for cycloaddition of germylene to the CC double bond of ethylene. The GeX2 + C2H4 (GeX2 = GeH2, Ge(CH3)2, Ge(NH2)2, Ge(OH)2, GeF2, GeCl2, GeBr2, and GeCH2) systems are the subject of the present study. All the stationary points were determined at the B3LYP/6-31G* level of theory. The major conclusions that can be drawn from this work are as follows:  (i) In contrast to the case of the carbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
30
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 37 publications
9
30
0
Order By: Relevance
“…72 However, this complex was found in previous quantum chemical studies using MP2 valence only calculations in conjunction with an effective core potential 84 and also in B3LYP/6 31G* calculations. 85 Because the QCISD method provides a better treatment of electron correlation than MP2, its prediction of the existence of the π complex seems reliable, and is in agree ment with the results of DFT calculations.…”
Section: Methodssupporting
confidence: 54%
“…72 However, this complex was found in previous quantum chemical studies using MP2 valence only calculations in conjunction with an effective core potential 84 and also in B3LYP/6 31G* calculations. 85 Because the QCISD method provides a better treatment of electron correlation than MP2, its prediction of the existence of the π complex seems reliable, and is in agree ment with the results of DFT calculations.…”
Section: Methodssupporting
confidence: 54%
“…15) and the much more reactive GeH 2 (see and GeMe 2 (see Refs 15 and 19 and notes in Ref. 17) proceed in a stepwise manner and begin with a barrierless formation of a π complex, which then undergoes transformation to a germirane (germacyclopropane).…”
Section: Gecl 2 Reactions With Ethylene and Buta 13 Dienementioning
confidence: 99%
“…The salient features of dihalogermylenes include a relatively low exothermicity of the formation of π complexes, high activation energy of the reaction, and endothermicity of formation of the cor responding 1,1 dihalogermirane. 14, 15 The results obtained in Ref. 15 revealed a low probability of the formation of 1,1 dichlorogermirane in the reaction of ethylene with GeCl 2 and suggested that it is π complexes rather than 1,1 dichlorogermiranes that participate as intermediates in the reactions of GeCl 2 with alkenes.…”
Section: Gecl 2 Reactions With Ethylene and Buta 13 Dienementioning
confidence: 99%
See 1 more Smart Citation
“…The addition of GeH 2 to the triple bond of acetylene occurs barrierlessly in one step unlike the reactions of germylenes with olefins which usu ally involve formation of a π complex. [18][19][20] Recently, 20 we reported a PBE 21 density functional study of the reactions of GeH 2 and GeMe 2 with olefins and buta 1,2,3 trienes and showed that the overall stabil ity of the product, germacyclopropane (germirane), is de termined by its stability to retrocycloaddition into initial reactants and to a rearrangement similar to rearrange ment (b) in Scheme 1. Taking the stable germirane 10 as an example, we determined the effects of the olefin structure and the nature of the substituents at the Ge atom on the stability of the germacyclopropane system.…”
mentioning
confidence: 99%